Squamous Cell Cancer Arising in an African American Male Cheek from Discoid Lupus: A Rare Case and Review of the Literature - Emanuel A. Shapera; Paul D. Kim (Case Reports in Surgery)
A 50-year-old African American male with Discoid Lupus Erythematosus (DLE) presented to the dermatology clinic for a rapidly enlarging left cheek mass. The mass failed to resolve with conservative measures. A biopsy revealed poorly differentiated Squamous Cell Carcinoma (SCC). He was referred to Head and Neck Surgery and successfully underwent a resection with free flap reconstruction. Postoperatively he did well. Squamous cell skin carcinomas arising from lesions of Discoid Lupus are rare and aggressive tumors with greater likelihood of metastases. Cases have been reported among patients with different clinical characteristics; we present a rare case arising in an African American male on the face and involving the ear.